Rewilding as Re-Enchantment - De Vroey, Linde (Religions, 2024)
Rewilding is regularly connected to re-enchantment. In some rewilding projects, ecological restoration merges with narratives of wonder, enchantment and spirituality. While rewilding’s association with re-enchantment appears as part of its appeal, it is also criticised as anthropocentric, escapist or naive. This article aims to formulate a thorough conceptual understanding of rewilding as re-enchantment by situating it within the critical framework of (dis)enchantment developed in the early 20th century by Weber and Horkheimer and Adorno. Connecting this framework to contemporary, phenomenologically inspired accounts of enchantment and critiques on the mechanisation of nature, this article aims towards a new perspective on rewilding as a critical discursive practice of re-enchantment. Rewilding, like re-enchantment, can be seen as a valuable attempt to formulate alternatives to the modern paradigm and programme of disenchantment. Situating rewilding within a broader cultural context and historical perspective, this approach allows for assessing rewilding as part of modern (counter-)culture at large. Moreover, through a detailed account of (re-)enchantment in rewilding on a phenomenological, theoretical and relational level, this article gradually develops a conceptual understanding of re-enchantment as a valuable concept for ecological restoration and cultural transformation.